PROSES PEMBUATAN SERAT MIKROBIAL (NATA) DARI LIMBAH CAIR PABRIK KELAPA SAWIT - Sarono, Zulfahmi, dan Syamsu Akmal (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Processing palm oil fruit into crude palm oil (CPO) produces liquid waste (palm oil mill effluent = POME) in large quantities. Besides potential as an environmental pollutant, POME also has a potential as a source of microbial fibers. The objectives of this study wereto determine the formulation of the addition of coconut water into POME in the production of microbial fiber (nata) and to determine the right timing for inoculation of Acetobacter xylinum in the production of microbial fiber (nata). The first factor was the time of keeping the POME, with a level of 7 days, 14 days, and 21 days. The second factor was the addition of coconut water with a level of 0%, 10%; 20%; 30%; and 40% of the total POME. The results of the study were the addition of coconut water into POME to a concentration of 40% was able to increase the thickness and fiber yield of microbial (nata), Acetobacter xylinum was able to grow on media of 100% POME, and keeping the POME up to 21 days could decrease the thickness and yield of wet microbial fibers (nata), but increase the microbial yield of dry fiber (nata) generated.Keywords: CPO, microbial fibers, nata, POME